Electrografting of BTSE: Zn films for advanced steel-aluminum joining by plastic deformation - Duderija, B.; González-Orive, A.; Schmidt, H.C.; Calderón, J.C.; Hordych, I.; Maier, H.J.; Homberg, W.; Grundmeier, G. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Untersuchung von Klebverbindungen für Batteriegehäuse - Schmolke, Tobias; Meschut, Gerson; Rieker, Florian; Meinderink, Dennis; Grundmeier, Guido (adhäsion KLEBEN & DICHTEN)

Nano-FTIR and chemical force analysis of electrografted aryldiazonium salts on ODT-microcontact printed Au-surfaces - Su, Jiangling; González Orive, Alejandro; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; de los Arcos, T.; Kollmann, S.; Carlet, M. (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Thin Organic‐Inorganic Anti‐Fouling Hybrid‐Films for Microreactor Components - Neßlinger, Vanessa; Welzel, Stefan; Rieker, Florian; Meinderink, Dennis; Nieken, Ulrich; Grundmeier, Guido (Macromolecular Reaction Engineering)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Influence of surface activation on the microporosity of PE‐CVD and PE‐ALD SiO x thin films on PDMS - Hoppe, Christian; Mitschker, Felix; Mai, Lukas; Liedke, Maciej Oskar; de los Arcos de Pedro, Maria Teresa; Awakowicz, Peter; Devi, Anjana; Attallah, Ahmed Gamal; Butterling, Maik; Wagner, Andreas; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos de Pedro, Maria Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas D.; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Comparative analysis of hexamethyldisiloxane and hexamethyldisilazane plasma polymer thin films before and after plasma oxidation - Xie, Xiaofan; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos, Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas; Grundmeier, Guido (Applied Surface Science)
Near ambient pressure XPS in nitrogen atmosphere was utilized to investigate gas-solid interactions within porous SiO2 films ranging from 30 to 75 nm thickness. The films were differentiated in terms of porosity and roughness. The XPS N1s core levels of the N2 gas in presence of the SiO2 samples showed variations in width, binding energy and line shape. The width correlated with the surface charge induced in the dielectric films upon X-ray irradiation. The observed different binding energies observed for the N1s peak can only partly be associated with intrinsic work function differences between the samples, opening the possibility that the effect of physisorption at room temperature could be detected by a shift in the measured binding energy. However, the signals also show an increasing asymmetry with rising surface charge. This might be associated with the formation of vertical electrical gradients within the dielectric porous thin films, which complicates the assignment of binding energy positions to specific surface-related effects. With the support of Monte Carlo and first principles density functional theory calculations, the observed shifts were discussed in terms of the possible formation of transitory dipoles upon N2 physisorption within the porous SiO2 films.
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

Enhancement of the delamination resistance of adhesive film coated surface laser melted aluminum 7075-T6 alloy by aminophosphonic acid adsorption - Vieth, P.; Garthe, M.-A.; Voswinkel, Dietrich; Schaper, Mirko; Grundmeier, Guido (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Influence of proteins on the corrosion of a conventional and selective laser beam melted FeMn alloy in physiological electrolytes - Huang, Jingyuan; Orive, Alejandro Gonzalez; Krüger, Jan Tobias; Hoyer, Kay-Peter; Keller, Adrian; Grundmeier, Guido (Corrosion Science)
Keywords: General Materials Science; General Chemical Engineering; General Chemistry

Microstructure and corrosion properties of PBF-LB produced carbide nanoparticles additivated AlSi10Mg parts - Kusoglu, Ihsan Murat; Vieth, Pascal; Heiland, Steffen; Huber, Florian; Lüddecke, Arne; Ziefuss, Anna Rosa; Kwade, Arno; Schmidt, Michael; Schaper, Mirko; Barcikowski, Stephan; Grundmeier, Guido (Procedia CIRP)
Keywords: General Medicine

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; Kollmann, S.; Carlet, M.; de los Arcos de Pedro, Maria Teresa (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Oxide Modified Iron in Electron Beam Powder Bed Fusion—From Processability to Corrosion Properties - Torrent, Christof J. J.; Krooß, Philipp; Huang, Jingyuan; Voigt, Markus; Ebbert, Christoph; Knust, Steffen; Grundmeier, Guido; Niendorf, Thomas (Alloys)
Additive manufacturing (AM) processes are not solely used where maximum design freedom meets low lot sizes. Direct microstructure design and topology optimization can be realized concomitantly during processing by adjusting the geometry, the material composition, and the solidification behavior of the material considered. However, when complex specific requirements have to be met, a targeted part design is highly challenging. In the field of biodegradable implant surgery, a cytocompatible material of an application-adapted shape has to be characterized by a specific degradation behavior and reliably predictable mechanical properties. For instance, small amounts of oxides can have a significant effect on microstructural development, thus likewise affecting the strength and corrosion behavior of the processed material. In the present study, biocompatible pure Fe was processed using electron powder bed fusion (E-PBF). Two different modifications of the Fe were processed by incorporating Fe oxide and Ce oxide in different proportions in order to assess their impact on the microstructural evolution, the mechanical response and the corrosion behavior. The quasistatic mechanical and chemical properties were analyzed and correlated with the final microstructural appearance.

Corrosion fatigue behavior of electron beam melted iron in simulated body fluid - Wackenrohr, Steffen; Torrent, Christof Johannes Jaime; Herbst, Sebastian; Nürnberger, Florian; Krooss, Philipp; Ebbert, Christoph; Voigt, Markus; Grundmeier, Guido; Niendorf, Thomas; Maier, Hans Jürgen (npj Materials Degradation)
Abstract Pure iron is very attractive as a biodegradable implant material due to its high biocompatibility. In combination with additive manufacturing, which facilitates great flexibility of the implant design, it is possible to selectively adjust the microstructure of the material in the process, thereby control the corrosion and fatigue behavior. In the present study, conventional hot-rolled (HR) pure iron is compared to pure iron manufactured by electron beam melting (EBM). The microstructure, the corrosion behavior and the fatigue properties were studied comprehensively. The investigated sample conditions showed significant differences in the microstructures that led to changes in corrosion and fatigue properties. The EBM iron showed significantly lower fatigue strength compared to the HR iron. These different fatigue responses were observed under purely mechanical loading as well as with superimposed corrosion influence and are summarized in a model that describes the underlying failure mechanisms.

Self-Assembled Fibrinogen Hydro- and Aerogels with Fibrin-like 3D Structures - Hense, Dominik; Büngeler, Anne; Kollmann, Fabian; Hanke, Marcel; Orive, Alejandro; Keller, Adrian; Grundmeier, Guido; Huber, Klaus; Strube, Oliver I. (Biomacromolecules)

Morphological Dynamics of Leukemia Cells on TiO2 Nanoparticle Coatings Studied by AFM - Garcia Diosa, Jaime Andres; Gonzalez Orive, Alejandro; Grundmeier, Guido; Camargo Amado, Ruben Jesus; Keller, Adrian (Applied Sciences)
Coatings of modified TiO2 nanoparticles (TiO2-m) have been shown to effectively and selectively trap non-adherent cancer cells, with an enormous potential for applications in photodynamic therapy (PDT). Leukemia cells have a remarkable affinity for TiO2-m coatings, adhering to the surface by membrane structures and exhibiting morphologic characteristics of amoeboid locomotion. However, the details of the cell–substrate interaction induced by the TiO2-m coating remain elusive. With the aim to obtain a better understanding of this phenomenon, leukemia cell adhesion to such coatings was characterized by atomic force microscopy (AFM) for short contact times up to 60 min. The cell and membrane morphological parameters mean cell height, contact area, cell volume, and membrane roughness were determined at different contact times. These results reveal cell expansion and contraction phases occurring during the initial stage of adhesion. Subsequently, the leukemic cells reach what appears to be a new resting state, characterized by pinning of the cell membrane by TiO2-m nanoparticle aggregates protruding from the coating surface.

Influence of thickness, homogeneity, and morphology of TiO2-m nanoparticle coatings on cancer cell adhesion - Garcia-Diosa, Jaime Andrés; Orive, Alejandro Gonzalez; Grundmeier, Guido; Keller, Adrian; Camargo-Amado, Rubén Jesús (Surface and Coatings Technology)

Nanoscale Surface Topography Modulates hIAPP Aggregation Pathways at Solid–Liquid Interfaces - Hanke, Marcel; Yang, Yu; Ji, Yuxin; Grundmeier, Guido; Keller, Adrian (International Journal of Molecular Sciences)
The effects that solid–liquid interfaces exert on the aggregation of proteins and peptides are of high relevance for various fields of basic and applied research, ranging from molecular biology and biomedicine to nanotechnology. While the influence of surface chemistry has received a lot of attention in this context, the role of surface topography has mostly been neglected so far. In this work, therefore, we investigate the aggregation of the type 2 diabetes-associated peptide hormone hIAPP in contact with flat and nanopatterned silicon oxide surfaces. The nanopatterned surfaces are produced by ion beam irradiation, resulting in well-defined anisotropic ripple patterns with heights and periodicities of about 1.5 and 30 nm, respectively. Using time-lapse atomic force microscopy, the morphology of the hIAPP aggregates is characterized quantitatively. Aggregation results in both amorphous aggregates and amyloid fibrils, with the presence of the nanopatterns leading to retarded fibrillization and stronger amorphous aggregation. This is attributed to structural differences in the amorphous aggregates formed at the nanopatterned surface, which result in a lower propensity for nucleating amyloid fibrillization. Our results demonstrate that nanoscale surface topography may modulate peptide and protein aggregation pathways in complex and intricate ways.